Ambient air pollution and risk of congenital anomalies in England, 1991–1999. Issue 4 (9th October 2009) - Dolk, H; Armstrong, B; Lachowycz, K; Vrijheid, M; Rankin, J; Abramsky, L; Boyd, P A; Wellesley, D
Abstract : Objectives: To investigate whether there is an association between risk of congenital anomaly and annual ward level exposure to air pollution in England during the 1990s. Methods: A geographical study was conducted across four regions of England using population-based congenital anomaly registers, 1991–1999. Exposure was measured as 1996 annual mean background sulphur dioxide (SO2 ), nitrogen dioxide (NO2 ) and particulate matter (PM10 ) concentrations at census ward level (n=1474). Poisson regression, controlling for maternal age, area socioeconomic deprivation and hospital catchment area, was used to estimate relative risk for an increase in pollution from the 10th to the 90th centile. Results: For non-chromosomal anomalies combined, relative risks were 0.99 (95% CI 0.93 to 1.05) for SO2, 0.97 (95% CI 0.84 to 1.11) for NO2 and 0.89 (95% CI 0.75 to 1.07) for PM10 . For chromosomal anomalies, relative risks were 1.06 (95% CI 0.98 to 1.15) for SO2, 1.11 (95% CI 0.95 to 1.30) for NO2 and 1.18 (95% CI 0.97 to 1.42) for PM10 . Raised risks were found for tetralogy of Fallot and SO2 (RR=1.38, 95% CI 1.07 to 1.79), NO2 (RR=1.44, 95% CI 0.71 to 2.93) and PM10 (RR=1.48, 95% CI 0.57 to 3.84), which is of interest in light of previously reported associations between this cardiac anomaly and other air pollutants. Conclusions: While air pollution in the 1990s did not lead to sustained geographical differences in the overall congenital anomaly rate in England, further research regarding specific anomalies is indicated.